Impact of Grass Endophyte on Leaf Spot in Perennial Ryegrass Caused by Bipolaris sorokiniana and Subsequent Aphids’ Feeding Preference - Ziyuan Ma; Jia He; Youlei Shen; Yingde Li; Ping Wang; Tingyu Duan (Agriculture)
Grass endophytes (Epichloë) are important symbiotic microorganisms of perennial ryegrass, playing a vital role in plant resistance against various stresses. This study investigated the effects of grass endophyte on leaf spot disease caused by fungal pathogen Bipolaris sorokiniana and subsequent feeding preferences of aphids (Rhopalosiphum maidis) on perennial ryegrass, with a particular focus on how grass endophyte influence the interactions between pathogens and aphids. The results indicated that grass endophytes significantly increased the net photosynthetic efficiency of perennial ryegrass. The interactions among grass endophytes, pathogen, and aphids affected the activities of superoxide dismutase (SOD), peroxidases (POD), and catalase (CAT). Grass endophytes enhanced SOD and CAT activities in pathogen-infected ryegrass. While pathogen infection and aphid infestation decreased jasmonic acid (JA) and salicylic acid (SA) concentrations, grass endophyte increased SA levels. Correlation analysis revealed a negative relationship between shoot dry weight and plant transpiration rate, SOD, and CAT activities. Aphid feeding choice showed that grass endophytes attracted more aphid feeding when co-infected with pathogens. This preference correlated positively with H2O2 and SA levels but negatively with NO and JA concentrations. Overall, grass endophytes enhance perennial ryegrass resistance to leaf spot pathogens and aphids, offering a novel pest and disease management strategy in agriculture.